Navigating risks: insights on unrelated overseas renal transplantations from two Saudi centers - Hany M. El Hennawy; Omar Safar; Abdullah S. Al Faifi; Maryam H. El Hennawy; Balqees Alghamdi; Amani Ali; Manar Alqahtani; Mohammad F. Zaitoun; Sharifah A. Alasmari; Ahmed Serageldeen; Konstantinos Fourtounas; Mostafa Ayyad; et al. (BMC Nephrology)
Abstract Background Due to a shortage of cadaveric organs for transplantation, some Saudi patients seek to purchase kidneys in other countries. However, kidney transplantation (KT) abroad is often associated with negative outcomes. This study shared the experiences of two Saudi transplantation centers regarding unrelated KT overseas. Methods This retrospective comparative cohort study included patients who underwent commercial KT abroad (Group I) and local patients who received living unrelated KT between September 2017 and July 2024, with available follow-up for at least one year. The primary outcome was to compare the perioperative outcomes. The secondary outcome was to compare the cumulative graft survival between both groups using cox-regression analysis. Results Group I included 96 patients and group II included 108 patients. Group I had a statistically significant longer 30-day hospital stay (9.4 ± 1.6 vs. 7.9 ± 1 days, P < 0.001). Primary functioning graft was significantly lower in Group I (83.3% vs. 93.5%; p = 0.01). Group I was associated with statistically significant higher incidence of surgical site infection (SSI) (P = 0.03), lymphocele (P = 0.007) and UTI (P = 0.002). The 1-, 2-, 3-, and 5-year cumulative graft survivals were 80%, 79%, 74%, and 54%, respectively in group I compared to 98%, 97%, 90%, and 60%, respectively in group II. [HR = 2, 95% CI = 1.1–3.8, P = 0.02] Conclusion Commercial transplantation graft survival rates are lower, and overall outcomes are worse than those of traditional unrelated transplantation in the midterm. Educating patients about the risks associated with overseas KT and promoting public registration for deceased organ donation could help mitigate this practice. Clinical trial number Not applicable.